Upaya Manajemen Bimbingan Konseling dalam Meningkatkan Kedisiplinan siswa di Madrasah Ibtidaiyah Darut Tauhid Desa Mekar Sari Kecamatan Sungai Raya - Abdul Pandi; Fauzan; Zainal; Nurul; Sulaiman; Dewi; Suliyah; Sari; Wardah (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
The purpose of this research is to determine the efforts of counseling guidance management in improving student discipline at the Madrasah Ibtidaiyah Darut Tauhid, Bunga Sari village, Sungai Raya sub-district with the first main problem, planning counseling guidance in improving student discipline. Second, implementing counseling guidance in improving student discipline and third, evaluation. counseling guidance in improving student discipline at the Madrasah Ibtidaiyah Darut Tauhid, Mekar Sari Village, Sungai Raya District. The method used in this research is a descriptive method with a qualitative approach. The main data sources in this research are counselor teachers, school principals and deputy head of student affairs as one of the active components in management efforts obtained through interviews, observation and documentation. The results of this research show that first, the planning of the counseling guidance management effort, the preparation of administration must include all activities that will be carried out, such as the preparation of the counseling guidance work program, the preparation of the RPL, documents for home visit implementation activities, and determining the general pattern of the counseling guidance organization and the preparation of the organizational structure. Second, the planning that is made requires implementation by the counselor teacher in terms of guidance and counseling services, but the number of services implemented varies because the implementation of these service activities has adjusted to the needs of students at school. Third, the evaluation carried out by the counselor teacher is so that the aim of providing discipline can be achieved. achieved according to expectations and goals, it is hoped that students will be able to train, control, control themselves so that they are not influenced by things from outside, so that they always get used to implementing disciplined behavior.